Sum-rate maximization in MIMO NOMA system with imperfect CSI - Yanjing SUN; Yang LIU; Jiasi ZHOU; Qi CAO; Song LI (Tongxin xuebao)
In order to solve the problem of maximizing the sum rate under the constraints of transmission power limitation and users’ rates requirements,precoder and receiver were devised by combining multiple-input multiple-output (MIMO) and non-orthogonal multiple access (NOMA) based on imperfect channel state information (CSI).To take advantage of successive interference cancellation (SIC) techniques to eliminate interference from weak user’s signal,each data stream of the strong user needed to decode the corresponding weak user’s signal.Since the problem formed was non-convex,it was converted into the problem with the difference of two convex functions (D.C.) by using semi-positive definite programming and first-order Taylor expansion,and a penalty function was used to solve the constraint of the rank of the precoding covariance matrix.The simulation results show that compared with the orthogonal multiple access technology,the proposed D.C.algorithm can improve system sum rate.